ASUHAN KEPERAWATAN KELUARGA BAPAK M KHUSUSNYA IBU M DENGAN MASALAH DIABETES MELITUS DI WILAYAH RW 07 KELURAHAN LIMO - Rufaida Azzahra (2023)
Diabetes Mellitus is a metabolic disorder characterized by increased glucose levels due to lack of the hormone insulin, decreased insulin effect or both. One of the most important aspects of diabetes mellitus treatment is to prevent complications by facilitating the family to support them in achieving optimal health levels. This paper aims to provide nursing care to Mr. M's family, especially Ms. M with diabetes mellitus health problems. The research design used in this case is a descriptive research method with a case study approach in Diabetes Mellitus patients in RW 07 Kelurahan Limo. Data collection was carried out by interviews, observation and physical examination. Nursing problems found in cases were ineffective family health management, unstable blood glucose levels and ineffective family health maintenance. After carrying out nursing actions for 3x24 hours the results of the evaluation of all nursing problems can be resolved. Elderly and family are able to implement nursing actions in order to control blood sugar levels independently.